1993
DOI: 10.1177/019874299301800207
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Management Strategies: Are They Setting Events for Coercion?

Abstract: The purpose of this investigation was to explore the Patterson and Reid (1970) reciprocal/coercive interaction hypothesis as related to the classroom social interactions between teachers and students identified with severe behavior disorders. Additionally, four classroom behavior management strategies are identified as potential setting events for either coercive or positive reciprocal interactions between teachers and students. The literature reviewed indicates that teachers are more likely to attend to stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(66 citation statements)
references
References 38 publications
2
62
1
1
Order By: Relevance
“…This approach can be contrasted to traditional orientations that are notable for the high degree of external control that is maintained in dassrooms for this population (Knitzer et al, 1990;Shores, Gunter, & Jack, 1993). In this respect, the choicemaking strategy in our study is consistent with a widespread movement to identify effective alternatives to punishment and, in particular, to promote student initiative and individualized curricular interventions for reducing problem behaviors .…”
Section: Resultssupporting
confidence: 63%
“…This approach can be contrasted to traditional orientations that are notable for the high degree of external control that is maintained in dassrooms for this population (Knitzer et al, 1990;Shores, Gunter, & Jack, 1993). In this respect, the choicemaking strategy in our study is consistent with a widespread movement to identify effective alternatives to punishment and, in particular, to promote student initiative and individualized curricular interventions for reducing problem behaviors .…”
Section: Resultssupporting
confidence: 63%
“…Additionally, high-fidelity teachers in this study provided a more positive classroom climate as indicated by an average 4:1, praise-to-correction ratio; that is, high-fidelity teachers praised students for social behavior and academic performance four times more often than they corrected students' misbehavior. Contrary to recommended ratios of 3:1 or higher (Shores, Gunter, & Jack, 1993;Walker, Ramsey, & Gresham, 2004), low-fidelity classrooms in this study had an average praise-tocorrection ratio of 1:2, that is, teachers corrected students' misbehavior twice as often as they made positive statements about student social and academic performance (Table 6). Praise in moderate-fidelity classrooms (once every 53 sec) occurred at rates close to those in high-fidelity classrooms; however rates of correction were closer to low-fidelity classrooms, thereby decreasing the praise-to-correction ratio in moderate fidelity classrooms to 1.4:1 (Table 6).…”
Section: Discussioncontrasting
confidence: 56%
“…A number of studies of the spatial structure of the classroom focus on such issues as patterns of student seating, the physical proximity of students to teachers, patterns of physical circulation in the classroom, and the overall sense of atmosphere and order, and show that these factors can have a relatively small but significant effect on student engagement (MacAuley 1990;Rinehart 1991;Shores, Gunter, and Jack 1993;Walker and Walker 1991;Walker, Colvin and Ramsey 1995;Wolfgang 1996;Stewart and Evans 1997;Bettenhausen 1998;Quinn et al 2000;Wannarka and Ruhl 2008).…”
Section: Teacher Management Of Physical Conditions In the Classroommentioning
confidence: 99%